Health behaviours of pregnant women and gestational weight gains – a pilot study - Suliga, Edyta; Adamczyk-Gruszka, Olga K. (Medical Studies/Studia Medyczne, 2015)
Introduction: Abnormal weight gain during pregnancy may exert a negative effect on the development of the foetus, the course of pregnancy, and later the state of health of the mother and her baby. Due to the unfavourable health consequences of abnormal body weight gains in expectant mothers studies of the factors that determine the amount of these gains are important. Aim of the research : Evaluation of the relationship between health behaviours in pregnancy, nutritional status before pregnancy, selected socio-demographic factors, and gestational weight gain. Material and methods : The investigation included 274 women. Using a questionnaire, information was collected pertaining to the place of residence, age, body height and weight, cigarette smoking, and eating habits during pregnancy. The total weight gain during pregnancy was calculated as the difference between perinatal weight and pre-pregnancy body weight. Gestational weight gains were classified as low, recommended, or high. Results: Increased risk of high weight gain was associated with the consumption of alcoholic beverages (odds ratio (OR) = 2.82), especially beer (OR = 2.72), high consumption of products supplying proteins of animal origin (OR = 2.87), and overweight before pregnancy (OR = 3.37), as well as the delivery being the mother’s first, compared to the third and subsequent childbirth (OR = 4.17). Conclusions: This study indicates that there is a need for health education among females at reproductive age in order to reduce excess weight before conception, and promotion of adequate health behaviours in pregnancy, which would allow the maintenance of normal weight gain during this period.